RANCANG BANGUN TRANSMISI PADA MESIN PENGADUK BUMBU KERIPIK LUMPIA KAPASITAS 5KG - Albaihaki, Alarik; Apnena, Riri Damayanti (Jurnal Mahasiswa Terapan; Vol 1 No 3 (2025): Jurnal Mahasiswa Terapan, 2025)
The development of machine technology that makes it easier for humans to do things more easily and quickly has encouraged the world of micro, small and medium enterprises to develop their businesses. The process of designing this spring roll seasoning mixing machine, will use a transmission system as a speed regulator (rotation) and driving force. The transmission system used is using pulleys and V-belts as speed transfer and is supported by a motor as the driving force, making it suitable for use in spring roll seasoning mixing machines. The data collection method in research is observation and literature study. The data processing technique in this study is the "Design and Build" technique. In designing the transmission, the author makes a design using Autodesk Inventor Professional 2019 and performs manual calculations. After carrying out the transmission calculations, the calculation of the pulleys is 50.8 mm and 100 mm with a gear box ratio ratio of 1: 20 obtained with a speed of 700 rpm and a v-belt length up to 163.3 mm. After analyzing and selecting the transmission system, it can be concluded that the transmission used in the lumpia chips seasoning mixer machine uses a gearbox, then connected to the pulley and v-belt as a link to the main shaft.